2021
DOI: 10.1101/2021.06.30.450556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Darting across space and time: Parametric modulators of sex-biased conditioned fear responses

Abstract: Pavlovian fear conditioning is a widely used behavioral paradigm for studying associative learning in rodents. Despite early recognition that subjects may engage in a variety of behaviors that reflect the experimental parameters of a given protocol, the last several decades have seen the field narrow its focus to measure freezing as the sole indicator of conditioned fear. Additionally, unconditioned responses such as shock-related activity are rarely considered. We previously reported that female Sprague Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 39 publications
(63 reference statements)
3
22
0
Order By: Relevance
“… Fadok et al, 2017 used a unique two-component serial CS consisting of a 10 s tone followed immediately by a 10 s white noise ending with a 1 s shock and found that the initial component (tone) produced freezing, while the second component (noise) produced bursts of locomotion and jumping in mice. Gruene et al, 2015 reported that in rats a tone CS resulted in a similar burst of locomotion, labeled darting, and this was replicated in subsequent studies ( Colom-Lapetina et al, 2019 ; Mitchell et al, 2021 ). The results were interpreted as a competition between ‘active’ and ‘passive’ defenses.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“… Fadok et al, 2017 used a unique two-component serial CS consisting of a 10 s tone followed immediately by a 10 s white noise ending with a 1 s shock and found that the initial component (tone) produced freezing, while the second component (noise) produced bursts of locomotion and jumping in mice. Gruene et al, 2015 reported that in rats a tone CS resulted in a similar burst of locomotion, labeled darting, and this was replicated in subsequent studies ( Colom-Lapetina et al, 2019 ; Mitchell et al, 2021 ). The results were interpreted as a competition between ‘active’ and ‘passive’ defenses.…”
Section: Introductionmentioning
confidence: 69%
“…We conjecture that the movements seen by Totty et al, 2021 exclusively in animals that were conditioned were largely this type of movement. Further, it is likely that the flight behavior in rats observed by other groups ( Colom-Lapetina et al, 2019 ; Gruene et al, 2015 ; Mitchell et al, 2021 ) is this type of movement as Mitchell et al report that the majority of their CS-elicited darting occurs late in the CS presentation, about 7–10 s into a 30 s tone CS.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations